Spotting Fruit versus Picking Fruit as the Selective Advantage of Human Colour Vision. (April 2013) - Bompas, Aline; Kendall, Grace; Sumner, Petroc
The spatiochromatic properties of the red–green dimension of human colour vision appear to be optimized for picking fruit in leaves at about arms' reach. However, other evidence suggests that the task of spotting fruit from a distance might be more important. This discrepancy may arise because the task a system (e.g. human trichromacy) is best at is not necessarily the same task where the largest advantage occurs over the evolutionary alternatives (dichromacy or anomalous trichromacy). We tested human dichromats, anomalous trichromats and "normal" trichromats in a naturalistic visual search task in which they had to find fruit pieces in a bush at 1, 4, 8 or 12 m viewing distance. We found that the largest advantage (in terms of either performance ratio or performance difference) of normal trichromacy over both types of colour deficiency was for the largest viewing distance. We infer that in the evolution of human colour vision, spotting fruit from a distance was a more important selective advantage than picking fruit at arms' reach.